Determinant of Gen Z Student Entrepreneurial Interests - Eliza Noviriani; Andiyono; Muhammad Farisan Luthfi (Politeknik Ganesha Medan, 2026)
This applied research is a development of previous studies, namely testing the determinants of students’ entrepreneurial interest. The researcher expanded the study by conducting tests on vocational students by selecting quota samples and processing data using Partial Least Square (PLS). This is an effort to answer the challenges of new research exploration and support the analysis of students' entrepreneurial interest toward sustainable finance in the future. The method used is a quantitative approach. Sample of the research are 144 students. The results of the exploration show that supporting factors influence students' entrepreneurial interest, while the variables of ambition for freedom and self-realization do not affect students' interest in entrepreneurship. It is due to the mindset of students who choose to work formally. In addition, the reality of the business climate in Sambas Regency, which is relatively undeveloped, also contributes to the lack of desire for students to become entrepreneurs. However, amid unstable economic conditions when jobs are limited, students' interest in entrepreneurship is influenced by pushing factors, including the role of universities, family, and colleagues. This study implies that universities can increase motivation, knowledge, and business information for students, especially Gen Z students so that students' interest in entrepreneurship increases.